Influence du sodium sur les propriétés physiques d'un sol aux niveaux textural et structural - Sigala F.; Fies J.C.; Guennelon R. (Reuse of low quality water for irrigation, 1989)
Using saline and non saline soils, experiments were conducted to evaluate the role of exchangeable Na+ on physical and mechanical properties of aggregates and clumps. At the same potentials, soils having more than 12.5 per cent ESP showed a higher moisture content than non saline or weakly Na-saturated soils. In the same manner, the more Na-saturated the soil is, the lower the moisture content of the shrinkage limit. The pores of sizes between 50 and 1,000 nm. induce a volume of void space for Na-soils greater than for the control sample. The mechanical resistance of dried clumps is greater for sodic than for non-sodic soils. On the contrary, the difference between both materials is unimportant as regards this mechanical property.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)